Basic ionic liquid functionalized magnetically responsive Fe3O4@HKUST-1 composites used for biodiesel production. (15th May 2018) - Xie, Wenlei; Wan, Fei
Graphical abstract: Highlights: Magnetic solid catalysts were used for biodiesel production in a heterogeneous manner. The catalyst could give the soybean oil conversion of 92.3%. The solid catalyst had a long-term catalytic activity. Abstract: The main purpose of this present work is to fabricate a magnetically recyclable solid catalyst for the production of biodiesel to meet the demand of green and clean production. To accomplish this, the core–shell structured Fe3 O4 @HKUST-1 composites with a magnetic core and a porous metal-organic framework shell were fabricated by using a versatile Layer-by-Layer assembly method, and then basic ionic liquids were encapsulated within the core–shell magnetically responsive material, resulting in a solid hybrid base catalyst. Various techniques such as XRD, TEM, FT-IR, VSM and nitrogen adsorption–desorption were employed to characterize the as-prepared solid base catalyst. The characterization results revealed that Fe3 O4 nanoparticles were well coated with metal-organic framework HKUST-1 with the formation of core–shell structured nanocomposites, and moreover the basic ionic liquid had been successfully encapsulated within the magnetic nanocomposites. Furthermore, the solid base catalysts possessed superparamagnetic behavior and high saturation magnetization, allowing them to be facilely separated from the reaction mixture by using an external magnetic filed. The solid base catalyst appeared to be an efficient and environmentally benign catalyst for the transesterification of soybean oil with methanol for the production of biodiesel, giving 92.3% oil conversion to methyl esters within 3 h with a catalyst loading of 1.2 wt% and a methanol/oil molar ratio of 30:1 at reflux temperature of methanol. The solid catalyst could be readily recovered by simple magnetic decantation and reused for several times without significant degradation in its catalytic activity.